2015
DOI: 10.1038/srep11083
|View full text |Cite
|
Sign up to set email alerts
|

Harbour porpoises react to low levels of high frequency vessel noise

Abstract: Cetaceans rely critically on sound for navigation, foraging and communication and are therefore potentially affected by increasing noise levels from human activities at sea. Shipping is the main contributor of anthropogenic noise underwater, but studies of shipping noise effects have primarily considered baleen whales due to their good hearing at low frequencies, where ships produce most noise power. Conversely, the possible effects of vessel noise on small toothed whales have been largely ignored due to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 50 publications
(71 reference statements)
2
54
2
1
Order By: Relevance
“…Both short-term (Thompson et al 2013a) and long-term displacement (Teilmann & Carstensen 2012) as well as changes in foraging behaviour (Pirotta et al 2014) have been reported as likely consequences of construction-related activity to this species. In addition, harbour porpoises are also likely to actively avoid vessels (Hermannsen et al 2014, Dyndo et al 2015; however, despite the present study finding evidence of constructionrelated activity reducing porpoise occurrence in the bay, it did not find any such pattern with respect to the number of vessels within the bay. Conversely, an increase in vessel numbers did have a strong, negative influence on the occurrence of common dolphins.…”
Section: Discussioncontrasting
confidence: 55%
“…Both short-term (Thompson et al 2013a) and long-term displacement (Teilmann & Carstensen 2012) as well as changes in foraging behaviour (Pirotta et al 2014) have been reported as likely consequences of construction-related activity to this species. In addition, harbour porpoises are also likely to actively avoid vessels (Hermannsen et al 2014, Dyndo et al 2015; however, despite the present study finding evidence of constructionrelated activity reducing porpoise occurrence in the bay, it did not find any such pattern with respect to the number of vessels within the bay. Conversely, an increase in vessel numbers did have a strong, negative influence on the occurrence of common dolphins.…”
Section: Discussioncontrasting
confidence: 55%
“…Dolphins living in human‐dominated coastal environments may be detrimentally effected by acoustic masking of important informational signals at these micro to fine scales (particularly if vessel noise is within the species’ hearing range; Dyndo et al . , Veirs et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…4 & 6; clearly at the 14−16 km range and likely also at the 8 km range). This reduction above 1 kHz is particularly interesting with respect to impact on harbour porpoises, as thresholds for negative phonotaxis are strongly frequency dependent ) and a strong correlation between reactions in captive porpoises to passing ships and frequency content above 1 kHz has been demonstrated (Dyndo et al 2015). If the energy above 1 kHz is also more important than the low frequencies for pile-driving noise, it becomes important to account for the spectral content of the noise in the assessment and regulation of the impact of pile driving.…”
Section: Discussionmentioning
confidence: 99%